The impact of AKEPT’s programmes in teaching and learning - Nordin, Mohamad Sahari; Ibrahim, Mohd Burhan; Abdul Rahman, Zainurin; Othman, Joharry; Syed Hassan, Syed Najmuddin; Smith, Brenda M. (s.n., 2013)
This study was conducted to asses the impact of AKEPT’s Centre for Leadership in Learning and Teaching in facilitating and sustaining high quality instructional leadership through capacity building interventions. Among others, the objectives of this impact assessment project were to review the curriculum, levels of participations as well as to examine the behavioral impacts as reported by the participants of programs conducted at the \centre. For data gathering, documents related to programs which were conducted in the past were analyzed in audition to a survey which was carried out on participants who have participated in various intervention programs conducted at the Centre. In this report, findings from both the qualitative and quantitative analysis are discussed and recommendations are made.